Sosialisai Pembuatan Pupuk Organik Kotoran Sapi - Andri, Andri; M, Leony Agustine (Lembaga Dongan Dosen, 2023)
Cow dung has been used as plant fertilizer. However, the usual use does not go through the process of making organic fertilizer first. So the utilization made is not optimal. So, it is necessary to process it first so that the organic element content in the manure can be produced optimally and can be of better benefit to the plants. This community service aims to provide training and make organic cow dung fertilizer for farmer groups. This activity went smoothly and the participants responded very well. Participants were very enthusiastic in responding during this activity. Many questions were asked, especially those related to organic cow dung fertilizer. The results of the evaluation carried out on making organic cow dung fertilizer can now be applied to cultivated plants.